Cadre training according to Ho Chi Minh ideology: a case study on cadres of Civil Affairs Committee of Provincial People’s committees (Journal of Contemporary Educational Policies and Practices, 2020)
Cadre training is one of the important stages in our Party’s human resource tasks. This is a very difficult and complex process, requiring both scientific and artistic approaches. In light of the above problems, the study of Ho Chi Minh Ideology on cadres fostering and application into the current Party’s cadres training is of extreme importance and necessity. In the article, the author focuses on clarifying the basic contents of Ho Chi Minh Ideology on developing cadres and the practical application in training cadres who are members of the Civil Affairs Committee of the Provincial People’s Committee.
Keywords: Fostering cadres; Ho Chi Minh ideology; party committee; provincial people’s committee